2010
DOI: 10.1021/jp103199x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Promoted Chlorination of RuO2(110)

Abstract: High resolution core level photoemission spectroscopy and temperature programmed reaction experiments together with density functional theory calculations were used to elucidate the chlorination mechanism of ruthenium dioxide RuO 2 (110) by hydrogen chloride exposure on the atomic scale. The surface selective chlorination accounts for the extraordinary stability of the RuO 2 catalyst in the Sumitomo process -the heterogeneously catalyzed oxidation of hydrogen chloride by oxygen. The selective replacement of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 25 publications
(43 reference statements)
2
49
0
Order By: Relevance
“…A few of the Cl ot atoms, which cannot desorb, remain on the surface, but can be incorporated into the bridging vacancies. [64][65][66] With an HCl exposure of 1.5 L, the total ratio of on-top O desorbing at 420 K and those at 700 K is 1 : 1, roughly reconciling the experimentally found ratio in TPR. The number of produced Cl 2 molecules equals the number of oxygen molecules produced from trapped O.…”
Section: Catalysis Science and Technology Perspectivesupporting
confidence: 77%
See 1 more Smart Citation
“…A few of the Cl ot atoms, which cannot desorb, remain on the surface, but can be incorporated into the bridging vacancies. [64][65][66] With an HCl exposure of 1.5 L, the total ratio of on-top O desorbing at 420 K and those at 700 K is 1 : 1, roughly reconciling the experimentally found ratio in TPR. The number of produced Cl 2 molecules equals the number of oxygen molecules produced from trapped O.…”
Section: Catalysis Science and Technology Perspectivesupporting
confidence: 77%
“…24 Upon exposure to HCl molecules at temperatures above 500 K, the stoichiometric RuO 2 (110) surface is transformed into a chlorinated surface where the bridging O atoms are partially replaced by chlorine. [64][65][66] The surface reaction of HCl oxidation over surface chlorinated RuO 2 (110) is summarized by the catalytic cycle depicted in Fig. 6.…”
Section: Mean Field (Mf) Based Microkinetic Modeling Has Been Applied...mentioning
confidence: 99%
“…In the case of RuO 2 (110) it was found that the anionic sublattice at the RuO 2 (110) surface of the catalyst is modified under reaction conditions in that the bridging surface O atoms (O br ) are selectively replaced by chlorine (Cl br ), one of the key factors to stabilize this oxide catalyst against corrosion [67][68][69]. Actually this substitution of surface oxygen sites at the RuO 2 (110) surface by chlorine has been shown not only to improve the stability of the catalyst but also to modify slightly the activity of the catalyst [66].…”
Section: Configurationmentioning
confidence: 99%
“…The main advantage of this catalyst is its high activity in the oxidation of HCl, so the reaction temperature can be reduced to about 300 • C. At 300 • C, in-depth chlorination is suppressed due to selective and self-limiting surface chlorination, and hence RuO 2 -based catalysts are quite stable [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%